3D Nanocomposite with High Aspect Ratio Based on Polyaniline Decorated with Silver NPs: Synthesis and Application as Electrochemical Glucose Sensor - Vasileva, Anna A.; Mamonova, Daria V.; Mikhailovskii, Vladimir; Petrov, Yuri V.; Toropova, Yana G.; Kolesnikov, Ilya E.; Leuchs, Gerd; Manshina, Alina A. (Nanomaterials, 2023)
In this paper, we present a new methodology for creating 3D ordered porous nanocomposites based on anodic aluminum oxide template with polyaniline (PANI) and silver NPs. The approach includes in situ synthesis of polyaniline on templates of anodic aluminum oxide nanomembranes and laser-induced deposition (LID) of Ag NPs directly on the pore walls. The proposed method allows for the formation of structures with a high aspect ratio of the pores, topological ordering and uniformity of properties throughout the sample, and a high specific surface area. For the developed structures, we demonstrated their effectiveness as non-enzymatic electrochemical sensors on glucose in a concentration range crucial for medical applications. The obtained systems possess high potential for miniaturization and were applied to glucose detection in real objects—laboratory rat blood plasma.
CRIS-Team Scopus Importer:2023-04-14
Keywords: anodic aluminum oxide; glucose sensor; laser-induced deposition; polyaniline